Wake Up, Work on Dreams, Back to Bed and Lucid Dream: A Sleep Laboratory Study - Erlacher, Daniel; Stumbrys, Tadas (Frontiers in Psychology, 2020)
Lucid dreams are defined as dreams in which the dreamer is aware of the fact that he or she is dreaming. This specific dream state offers many opportunities to study consciousness processes. However, lab research in this area is limited because frequent lucid dreamers are rare. A considerable number of studies demonstrated that different methods of induction could increase the number of lucid dreams. In four field studies a combination of a wake-up-back-to-bed sleep protocol and a mnemonic technique showed promising results. To further investigate the effectiveness of this technique, we conducted a series of sleep laboratory experiments with polysomnographic recording (PSG) with people who were not selected by their lucid dream abilities. For each experiment, participants spent a single night in a sleep laboratory. After 6 hours of sleep, they were awakened from a subsequent REM period and kept awake for 1 hour, during which they were asked to do a dreamwork and practice MILD. Then they returned to bed for a morning sleep period. In the first Experiment eleven sport students, who attended a seminar on sleep and dreams, participated. To avoid biases due to the seminar attendance (e.g. greater interest or higher motivation), in the second experiment 15 participants who did not attend the seminar were recruited. In the third experiment, 14 sport students accomplished the same procedure but with a shorter awakening period (of about 40 min instead of 1 hour). Finally, in the fourth and fifths experiment, we tested if the activity, which is carried out during the period of awakening, is important. This time eleven sport students spent two non-consecutive nights in a sleep laboratory. Instead of doing a dreamwork, in one night the participants read a book (fiction, unrelated to dreams), while in the other they played a Wii video game involving a balancing exercise. The order of nights was counterbalanced. In the first three experiments, six (54%), eight (53%) and five participants (36%) reported lucid dreams during the morning sleep period. Whereas thr